Pulsed Light Accelerated Crosslinking versus Continuous Light Accelerated Crosslinking: One-Year Results - Cosimo Mazzotta; Claudio Traversi; Anna Lucia Paradiso; Maria Eugenia Latronico; Miguel Rechichi (Journal of Ophthalmology)
Purpose. To compare functional results in two cohorts of patients undergoing epithelium-off pulsed (pl-ACXL) and continuous light accelerated corneal collagen crosslinking (cl-ACXL) with dextran-free riboflavin solution and high-fluence ultraviolet A irradiation. Design. It is a prospective, comparative, and interventional clinical study. Methods. 20 patients affected by progressive keratoconus were enrolled in the study. 10 eyes of 10 patients underwent an epithelium-off pl-ACXL by the KXL UV-A source (Avedro Inc., Waltham, MS, USA) with 8 minutes (1 sec. on/1 sec. off) of UV-A exposure at 30 mW/cm2 and energy dose of 7.2 J/cm2; 10 eyes of 10 patients underwent an epithelium-off cl-ACXL at 30 mW/cm2 for 4 minutes. Riboflavin 0.1% dextran-free solution was used for a 10-minutes corneal soaking. Patients underwent clinical examination of uncorrected distance visual acuity and corrected distance visual acuity (UDVA and CDVA), corneal topography and aberrometry (CSO EyeTop, Florence, Italy), corneal OCT optical pachymetry (Cirrus OCT, Zeiss Meditec, Jena, Germany), endothelial cells count (I-Conan Non Co Robot), and in vivo scanning laser confocal microscopy (Heidelberg, Germany) at 1, 3, 6, and 12 months of follow-up. Results. Functional results one year after cl-ACXL and pl-ACXL demonstrated keratoconus stability in both groups. Functional outcomes were found to be better in epithelium-off pulsed light accelerated treatment together with showing a deeper stromal penetration. No endothelial damage was recorded during the follow-up in both groups. Conclusions. The study confirmed that oxygen represents the main driver of collagen crosslinking reaction. Pulsed light treatment optimized intraoperative oxygen availability improving postoperative functional outcomes compared with continuous light treatment.